Design of Pesticide Sprayers and Solar Lawn Mowers - Bimo Agressianto; Izza Anshory (Universitas Muhammadiyah Sidoarjo, 2022)
Pesticide sprayer for farmers is a tool that is needed for farmers in the fields and in the fields until now, but in its use, farmers still feel complaints about the use of pesticide sprayers that still use the manual method. these complaints are tools that are less ergonomic and are still outdated and also when farmers want to cut grass sometimes it is very complicated to carry sickles and also when cutting grass. The purpose of this research is to assemble a pesticide sprayer and lawn mower with appropriate solar energy. with farmers' needs and to find out how efficient this tool is for farmers. The result of this study is a modified working system, especially for pesticide sprayers, where a 12 Volt DC motor as a substitute for human power and a lawn mower also uses a 12 Volt DC motor as a blade driver and for power uses solar energy which requires solar cells or solar panels and then stored into Battre or battery . The total cost of making this tool is around IDR 700,000.00